The Effect of Storage Duration on Fat Deterioration and Sensory Quality of Beef Rendang at Dapoer Rendang Riry, Payakumbuh City - Susi Desminarti; Yanda Bhinnelka; Agustina Agustina (Green Engineering Society, 2026)
Rendang is a high-fat food product that is susceptible to quality deterioration during storage, particularly due to lipid oxidation and potential microbiological contamination resulting from inadequate packaging. This study investigated the effect of storage duration on the quality of beef rendang stored at room temperature, as indicated by fat deterioration, sensory changes, and microbiological quality. Beef rendang was stored for three months in vacuum-sealed aluminum foil packaging at room temperature. Monthly analyses included fat content, free fatty acid (FFA) levels, thiobarbituric acid (TBA) value, total plate count (TPC), initial spoilage assessment using the Eber test, and sensory evaluation of color, aroma, texture, taste, and overall appearance. Protein, moisture, and ash contents were determined at the beginning and end of storage to evaluate compliance with SNI 7764:2012. Protein was analyzed using the Kjeldahl method, while moisture and ash were determined gravimetrically in accordance with AOAC (2007) procedures. The results showed a gradual decline in product quality during storage. Fat content decreased from 27.00±0.16% to 20.95±0.43%, while FFA levels increased from 3.31±0.17% to 5.52±0.34%. The TBA value increased from 0.01±0.002 to 0.07±0.002 mg Ma/kg. Sensory attributes exhibited a decreasing trend over the storage period. No microbial growth, including Salmonella and Escherichia coli, was detected, and the Eber test indicated no ammonia formation. Protein, moisture, and ash contents remained within SNI limits. Overall, quality deterioration was mainly associated with lipid degradation, while the product remained safe and suitable for consumption throughout storage.